2014
DOI: 10.1149/2.011404ssl
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron Mobility of the Electron Transport Layer on Fluorescent Organic Light-Emitting Diodes

Abstract: The charge balance mechanism in green fluorescent organic light-emitting diodes is investigated for different electron transport layers (ETLs) and electron mobilities. Carrier accumulation and an increase in the exciton recombination probability are shown to be critical for improving the current and power efficiencies by aligning the bands at the interface between the emitting layer (EML) and ETL. The peak in the electroluminescence (EL) spectra was found to shift slightly in response to changes in the width o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…7. These phenomena are similar to the report of reference [27]. The potential barrier between the HOMO of the EML (CBP in this study) and that of TPBi is $0.6 eV, which induces carrier accumulation at the interface between EML and ETL, But the potential barrier of HOMO between CBP and Alq 3 is $0 eV.…”
Section: Effect Of Dopants Concentrations and Etl Materials In White supporting
confidence: 91%
See 3 more Smart Citations
“…7. These phenomena are similar to the report of reference [27]. The potential barrier between the HOMO of the EML (CBP in this study) and that of TPBi is $0.6 eV, which induces carrier accumulation at the interface between EML and ETL, But the potential barrier of HOMO between CBP and Alq 3 is $0 eV.…”
Section: Effect Of Dopants Concentrations and Etl Materials In White supporting
confidence: 91%
“…The potential barrier between the HOMO of the EML (CBP in this study) and that of TPBi is $0.6 eV, which induces carrier accumulation at the interface between EML and ETL, But the potential barrier of HOMO between CBP and Alq 3 is $0 eV. In reference [27], they found that the improved exciton recombination originates from carrier accumulation in the EML/ETL interface, which reduces the chance that carriers do not generate excitons in the EML; this also improves the current efficiency. The current efficiency of the TPBi device is slightly better than that of the Alq 3 device because of the higher HOMO level.…”
Section: Effect Of Dopants Concentrations and Etl Materials In White mentioning
confidence: 64%
See 2 more Smart Citations
“…In general holes are being transported very quickly, while the electron mobility's are smaller in polymeric semiconductors and this causes low exciton generation and current efficiency [40,41]. In order to study the effect of CIS/ZnS incorporation on charge injection into the system, electron-and hole-only devices based of bare ADS233YE and Fig.…”
Section: Device Characteristicsmentioning
confidence: 99%